2015
DOI: 10.1111/jgs.13459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wells and Revised Geneva Rule to Assess Pretest Probability of Pulmonary Embolism in High‐Risk Hospitalized Elderly Adults

Abstract: In high-risk elderly hospitalized adults, the Wells score is more accurate than the revised Geneva score for diagnosing PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
3
13
1
6
Order By: Relevance
“…Predictive values indicated that all rules were most useful in reducing the risk of PTE to less than 15% in patients categorised as having low‐risk scores. These findings are similar to those reported from other centres with a negative predictive value of 85–90% . However, in the absence of negative D‐dimer assays in all such cases, this risk of PTE is likely to remain unacceptably high for many clinicians who will subsequently request a CTPA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Predictive values indicated that all rules were most useful in reducing the risk of PTE to less than 15% in patients categorised as having low‐risk scores. These findings are similar to those reported from other centres with a negative predictive value of 85–90% . However, in the absence of negative D‐dimer assays in all such cases, this risk of PTE is likely to remain unacceptably high for many clinicians who will subsequently request a CTPA.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are similar to those reported from other centres with a negative predictive value of 85-90%. 30,31 However, in the absence of negative D-dimer assays in all such cases, this risk of PTE is likely to remain unacceptably high for many clinicians who will subsequently request a CTPA.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of PE poses a special challenge in the elderly, given that its prevalence increases with age, 4 as does the frequency of comorbid conditions that can present with similar signs and symptoms. Although the accuracy and clinical utility of prediction rules remain good in this population, 40,41 there is an age-dependent increase in D-dimer levels 42 that results in a decline in the specificity of D-dimer testing in the elderly when a conventional fixed cutoff is used. This can lead to high rates of unnecessary imaging in this group.…”
Section: Potential Benefits Of Implementing the Recommendationsmentioning
confidence: 99%
“…Modifikuota Geneva skalė paremta vien objektyviais klinikiniais kriterijais, todėl klinicisto subjektyvumas ir turima klinikinė patirtis neturi įtakos paciento įvertinimui (22). Manyta, kad PATE tikėtinumo nustatymas remiantis modifikuota Geneva skale yra objektyvesnis nei remiantis Wells skale (22), tačiau studijos, lyginusios šias skales tarpusavyje, Wells skalę nustatė esant jautresnę ir specifiškesnę nei modifikuota Geneva skalė (11,(23)(24)(25). Nedaug studijų lygino šių skalių prognostinę vertę diagnozuojant PATE senyvo amžiaus pacientams (23).…”
Section: Rezultatų Aptarimasunclassified